Samsung Galaxy Tab - Hart-Davis, Guy (New York McGraw-Hill, 2012)
"Get the most out of your Samsung Galaxy Tab At last--a tablet that puts the power of a full computer right in your pocket! This hands-on guide shows you how to tap into your Galaxy Tab's full range of business productivity and entertainment features. How to Do Everything: Samsung GALAXY Tab teaches you how to connect to wireless networks, sync data with your PC or Mac, browse the Web, use e-mail, and much more. Harness the power of the Android operating system, maximize the built-in and third-party applications and maintain and troubleshoot your Galaxy Tab with help from this practical, time-saving resource. Set up, navigate, and customize your Galaxy Tab Connect seamlessly to as many wireless networks as you need Synchronize your Galaxy Tab with your PC using Samsung Kies Integrate your Galaxy Tab with your Mac Make phone calls with enabled models and enjoy video conferencing Play movies on your Galaxy Tab or your TV Take photos and share them online and offline Check e-mail, communicate with instant messaging, and browse the Web from anywhere Keep up with your social networks on the go Read e-books and PDFs in the palm of your hand Navigate easily with Google Maps Install and use versatile applications from the Android Market Troubleshoot, maintain, and secure your Galaxy Tab "--
Includes index
1
Keywords: Samsung Galaxy Tab (Computer)